Pengaruh Metode Latihan dan Motivasi Berprestasi Terhadap Kemampuan Lay Up Shoot Permainan Bola Basket Ekstakulikuler Siswa SMP N 1 Watampone - Harliawan, Muhammad; Dos Santos, Maria Herlinda; Okilanda, Ardo (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
The purpose of this study is to determine the effect of the methods section training and methods overall training motivation achievement shoot lay-up skills in the game of basketball The research is conducted at extracurricular student SMP 4 Watampone ,This study is using treatment by level 2 x 2. The samples are consisted of 40 student. The technique of data analysis is two ways analysis of variance (ANAVA) and followed by Tuckey's test for significance level of α = 0, 05. The results of this study show that (1) score for method training section (A1) is higher than the method of overall training (A2) at extracurricular student SMPN 1 Watampone ; (2) there is an interaction between practice methods (A) and training motivation (B) shoot lay-up skills in the game of basketball; (3) score of high method section training (A1B1) is higher than score of high method overall training (A2B1); 4) score of low method section training (A1B2) is lower than score of low method overall training (A2B1)